2017
DOI: 10.1161/atvbaha.116.308253
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Fibrin Clot Phenotype Is Associated With Recurrent Pulmonary Embolism After Discontinuation of Anticoagulant Therapy

Abstract: Objective-Pulmonary embolism (PE) is a life-threatening manifestation of venous thromboembolism with a high recurrence rate after anticoagulation cessation. Recently, we have reported that prothrombotic clot phenotype in venous thromboembolism patients is associated with an increased risk of recurrent deep-vein thrombosis. Approach and Results-We tested whether abnormal clot properties are predictive of recurrent PE. We investigated 156 consecutive white patients aged 18 to 65 years after the first-ever provok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 27 publications
2
48
0
1
Order By: Relevance
“…37 Thus, the substantially thinner fibers observed at high thrombin concentrations in earlier studies may reflect fiber compaction or shrinkage that occurs during dehydration. Regardless, the association of fibrin clot structural parameters with clinical pathologies – dense networks of thinner/compact fibers with increased thrombotic risk 3840 and coarse networks of thicker/less compact fibers with increased bleeding risk 36,41 – suggests fibrin structure is a critical determinant of hemostasis and thrombosis.…”
Section: Fibrin Formation Structure and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…37 Thus, the substantially thinner fibers observed at high thrombin concentrations in earlier studies may reflect fiber compaction or shrinkage that occurs during dehydration. Regardless, the association of fibrin clot structural parameters with clinical pathologies – dense networks of thinner/compact fibers with increased thrombotic risk 3840 and coarse networks of thicker/less compact fibers with increased bleeding risk 36,41 – suggests fibrin structure is a critical determinant of hemostasis and thrombosis.…”
Section: Fibrin Formation Structure and Stabilitymentioning
confidence: 99%
“…3840 Following percutaneous coronary intervention, patients who develop in-stent thrombosis demonstrate abnormal plasma clot characteristics (e.g., permeability, turbidity, lysis time) compared to patients who did not develop in-stent thrombosis. 112 Similarly, compared to healthy controls, plasma clots from patients with abdominal aortic aneurysm have more densely-packed fibrin networks with smaller pores, and were more resistant to lysis.…”
Section: Abnormal Fibrinogen and Fibrin Structure In Thrombosismentioning
confidence: 99%
“…In 2017, we observed that recurrent PE, diagnosed during follow -up in 23 patients (5% per year) following the first--ever provoked or unprovoked PE, is associated with formation of denser fibrin networks, as evidenced by reduced K s (HR, 1.82; 95% CI, 1.01-3.13; FIguRE 3). 65 Postthrombotic syndrome is a common complication of DVT that has been found to be associated with K s reduced by 11.7% when assessed 3 months after the index DVT. 66 Recurrent VTE occurred also more commonly in patients with postthrombotic syndrome, who were characterized by lower K s and prolonged clot lysis time (CLT).…”
mentioning
confidence: 99%
“…Although APS patients compared to healthy controls have increased clot‐bound β2GPI, the mechanism by which aPL antibodies can modulate fibrin properties remains unclear. Since (pro)thrombin is a known modulator of fibrin clot characteristics, the current study was designed to evaluate aPS/PT antibodies as potential determinants of reduced clot permeability and susceptibility to lysis in patients with thrombotic APS.…”
Section: Introductionmentioning
confidence: 99%